Corporate environmental publicity and green innovation: are words consistent with actions? - Huisu Lai; Lei Quan; Fei Wu; Song Tang; Chong Guo; Xiaobing Lai (Humanities & Social Sciences Communications)
Abstract Corporate environmental publicity is a vital tool for enhancing a company’s image and strengthening information exchange, significantly impacting corporate green development. Using a dataset of Chinese A-share listed companies from 2008 to 2020, we investigated the influence of corporate environmental publicity on green innovation. The results indicate that while corporate environmental publicity increases overall patent output, this growth is primarily driven by strategic rather than substantive green innovation. Further analysis reveals that corporate environmental publicity behaviors, motivated by greenwashing, reputation mechanisms, environmental subsidies, and R&D manipulation, lead to these outcomes. Notably, we found that heavily polluting enterprises are more adversely affected by this phenomenon, whereas ISO 14001 environmental certification and government regulation can mitigate the inconsistency between corporate environmental publicity and actual practices, thereby promoting substantive environmental actions. This study extends the research on factors influencing green innovation, aiming to minimize the negative effects of corporate environmental publicity.